Gate-tunable phase transition in a resonator-based Su-Schrieffer-Heeger chain - Lukas Johannes Splitthoff; Miguel Carrera Belo; Guliuxin Jin; Yu Liu; Eliska Greplova; Christian Kraglund Andersen (Physical Review Research)
Metamaterials engineered to host topological states of matter in controllable quantum systems hold promise for the advancement of quantum simulations and quantum computing technologies. In this context, the Su-Schrieffer-Heeger (SSH) model has gained prominence due to its simplicity and practical applications. Here we present the implementation of a gate-tunable, five-unit-cell resonator-based SSH chain on a one-dimensional lattice of superconducting resonators. We achieve electrostatic control over the inductive intracell coupling using semiconductor nanowire junctions, which enables the spectroscopic observation of a transition from a trivial to a topological phase in the engineered metamaterial. In contrast to prior work, our approach offers precise and independent in situ tuning of the coupling parameters, which is critical to directly approximate ideal tight-binding Hamiltonians via the control over local variables. Our results supplement efforts towards gate-controlled superconducting electronics and large controllable resonator-based lattices to enable quantum simulations.